Meningkatkan Partisipasi Anak Dalam Kegiatan Tahsin Di Luar Jam Sekolah: Upaya Pengabdian Mahasiswa Kuliah Kerja Nyata Di Desa Tanjung Mulia - Manik, Wahyuni (EL-EMIR INSTITUTE, 2026)
Tahsin activities, designed to improve Quran recitation, are an essential part of Islamic religious education. However, in Tanjung Mulia Village, low attendance of children in tahsin activities outside of school hours was identified. These activities are often considered boring, and some children fear the strict tahsin teachers, which reduces their motivation to learn. The Community Service Program (KKN) at the University of Muhammadiyah North Sumatra was implemented to address this problem through a participatory and educational approach. The methods used included observation, interviews with Quran teachers and parents, and the implementation of interactive learning methods based on Islamic educational games, positive rewards, and training tahsin teachers to be more friendly and communicative. The results showed an increase in student attendance from 30% to 70%, as well as an increase in reading ability of the hijaiyah alphabet and basic reading rules by up to 80%. Furthermore, children's fear of tahsin teachers was reduced due to the more enjoyable and appreciative learning environment. Supporting factors for success included family involvement through the